Efektivitas Efektivitas Metode Pembelajaran SQ4R Dalam Menyimpulkan Isi Teks Pidato Pada Mata Pelajaran Bahasa Indonesia Di SMPN 2 Tambelangan : Efektivitas - Shodiqin; Asri Bariqoh; Amirul Mukminin (Jurnal Cendekia Pendidikan, 2024)
Aiming to find out how active the speech writing ability of class VII students at SMPN 2 Tambelangan semester 1 is, this research uses quantitative research. The variables of this research are the use of the SQ4R learning method as the independent variable and concluding the content of the text of the speech in class VII SMPN 2 Tambelangan after the learning process takes place as the dependent variable. The learning results concluded that the content of the pinato text in the experimental class had increased greatly. The normality test results obtained a value of p= 0.841 for the experimental class and p= 0.573 for the control class. Provided that if the p value > α= 0.05 then the data comes from normally distributed data. Data from SPSS analysis shows a p value= 0.841 > α= 0.05 in the experimental class and a p value= 0.573 > α= 0.05 in the control class. This shows that the use of the SQ4R learning method is effective in learning Indonesian in particular on the basic reading competency of students at SMPN 2 Tambelangan Birem Tambelangan SPSS data analysis.